Radiological monitoring of Malaysian oil and gas industries - Amin, Y.M.; Nik, H.W. (Institut Fizik Malaysia, 2004)
Naturally occurring radioactive materials (NORM), especially Ra-226 and Ac-228 and their decay products are found to have high concentration in oil sludge and scales. The deposition of scales containing radium isotopes are high in items where there are changes in pressure and temperatures such as production tubes, valves, separator vessels and oily water treatment unit. As part of the requirement of Malaysian Atomic Energy Licensing Board (AELB), radiological monitoring of NORM contaminated oil production equipment are required. The immediate environment such as discharge water and air is also monitored. The parameters measured included the concentration of Ra-226, Ac-228 and Po-210. The concentration of radon and thoron are also measured. Thermoluminecence dosimeters (TLD) is used to measure accumulated external radiation while gross alpha and beta detector are used to measure surface contamination. The mean activity of the sludge is found to be 2.45 ± 1.29 Bq/g while the level of Po-210 is found to be 0.165 ± 0.019 Bq/g. The radon and thoron concentration in air is below the detection level of 0.0005 WL. The accumulated external radiation is found to be 0.12-0.21 µSv/h and 0.07-0.11 µSv/h for offshore and onshore respectively.